PENERAPAN PRINSIP-PRINSIP DEMOKRASI ANGGOTA LEGISLATIF DI KABUPATEN SINJAI PADA ERA PANDEMI COVID-19 - Sukarno Hatta; Syahril Syahril; Abd Wahid; Zulhidayat H. Zulfikar (Program Studi Administrasi Publik, 2022)
This study aims to determine the application of the democratic principles of legislative members in Sinjai Regency in the era of the Covid-19 Pandemic. This type of research is qualitative, data collection techniques are observation, interviews and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the democratic principles of the members of the DPRD of Sinjai Regency during the Covid-19 pandemic went well and was not affected by the pandemic. This can be seen from the continued fulfillment of democratic principles. Settlement of disputes is carried out peacefully and institutionally with reference to decision making based on the rules of the DPRD of Sinjai Regency, persuasive steps and mediation through the Honorary Board of the DPRD of Sinjai Regency. In responding to changes that occur in society, members of the Sinjai DPRD encouraged the Sinjai Regency Government to take quick steps in reducing the impact of the Covid-19 pandemic. In addition, it also educates the public to be able to make peace with the pandemic conditions and can understand the importance of preventing the transmission of Covid-19 through health protocols and social distancing. The implementation of the change of leadership in the Sinjai Regency DPRD is still carried out according to applicable regulations and the schedule that should be and is not affected by the Covid-19 pandemic. In addition, law enforcement always avoids the use of force. Members of the DPRD of Sinjai Regency also acknowledge and consider it natural that differences exist and consider these differences as a blessing, and strive to ensure the upholding of justice by escorting the distribution of social assistance and guarding the political rights of the community at the 2022 Simultaneous Village Head Election event.